2013
DOI: 10.1016/j.jsbmb.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in transcriptional effects of 1α,25 dihydroxyvitamin D3 on fibroblasts associated to breast carcinomas and from paired normal breast tissues

Abstract: The effects of 1α,25 dihydroxyvitamin D3 (1,25D) on breast carcinoma associated fibroblasts (CAFs) are still unknown. This study aimed to identify genes whose expression was altered after 1,25D treatment in CAFs and matched adjacent normal mammary associated fibroblasts (NAFs). CAFs and NAFs (from 5 patients) were cultured with or without (control) 1,25D 100 nM. Both CAF and NAF expressed vitamin D receptor (VDR) and 1,25D induction of the genomic pathway was detected through up-regulation of the target gene C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…As shown in Fig. 5C, all of the cell types display the VDR and thus may be responsible for the suppression of omental metastases by 1,25D 3 .1,25D 3 actions in adipocytes [28], fibroblasts [5] and immune cells [14,27] have been reported in the literature. Elucidation of the molecular mechanism underlying the suppression of EOC invasion mediated through stromal VDR relies on the identification of the main cell types in omental tumor microenvironment that mediate the 1,25D 3 action through the stromal VDR.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 5C, all of the cell types display the VDR and thus may be responsible for the suppression of omental metastases by 1,25D 3 .1,25D 3 actions in adipocytes [28], fibroblasts [5] and immune cells [14,27] have been reported in the literature. Elucidation of the molecular mechanism underlying the suppression of EOC invasion mediated through stromal VDR relies on the identification of the main cell types in omental tumor microenvironment that mediate the 1,25D 3 action through the stromal VDR.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this murine data, high content immunohistochemistry of normal human breast epithelium demonstrated that VDR positive cells are exclusively found in the luminal (differentiated) cell layer and do not co-localize with proliferating Ki67 positive cells (Santagata et al, 2014). VDR has also been identified in the stromal compartment including the mammary fibroblasts and adipocytes (Ching et al, 2011; Campos et al, 2013; Knower et al, 2013), highlighting the complexity of 1,25(OH) 2 D 3 signaling in the breast tissue environment.…”
Section: Vitamin D Pathway Expression In Normal Mammary Cells and Brementioning
confidence: 99%
“…Here we will focus on the few comprehensive genomic studies that have allowed for identification of vitamin D responsive pathways in breast cancer (Lee et al, 2006; Campos et al, 2013; Milani et al, 2013; Laporta and Welsh, 2013). In the first study of vitamin D mediated genomic changes in breast cancer, Feldman's groups used early generation arrays to compare gene expression in ER positive MCF-7 cells and ER negative MDA-MB-231 cells treated with 100 nM 1,25(OH) 2 D 3 (Swami et al, 2003).…”
Section: Genomic Profiling Of Vdr Agonists In Breast Cancer Model Sysmentioning
confidence: 99%
“…The mesenchymal origin of the cells was confirmed by the expression of vimentin and lack of expression of pan-cytokeratin and CD45. The culture conditions were as previously described (Rozenchan et al , 2009; Santos et al , 2011; Campos et al , 2013). αSMA expression was detected in all samples from primary tumor and lymph nodes and has been described in previous reports (Rozenchan et al , 2009; Santos et al , 2011; Campos et al , 2013).…”
Section: Methodsmentioning
confidence: 99%